Intramolecular noncovalent trans ring restricting free rotation of σ single bond enhances photosynthesis of hydrogen peroxide - Yaru Guo; Youxing Liu; Lu Li; Yachao Xu; Zheng Lin; Zongqiang Sun; Mingchuan Luo; Shaojun Guo; Xuliang Deng (Proceedings of the National Academy of Sciences, 2026)
Solar energy–driven hydrogen peroxide (H 2 O 2 ) synthesis from atmospheric oxygen and water represents a sustainable and highly promising avenue for the production of this essential chemical. Covalent organic frameworks (COFs) offer a molecular platform for the direct conversion of solar energy to H 2 O 2 , however, they are persistently plagued by the recombination of photogenerated charge carriers, a phenomenon induced by σ-bond rotation under light irradiation, which typically leads to sluggish conversion kinetics and suboptimal efficiency. We herein present a molecular engineering strategy involving the construction of noncovalent trans rings (Nc-TRs) within COFs. This approach entails the precise introduction of noncovalent interactions between donor and acceptor moieties, thereby constraining the free rotation of σ bonds and substantially suppressing the recombination of photogenerated charge carriers. Experimental and theoretical investigations demonstrate that the incorporation of Nc-TR within TAPT-DHBD COFs reduces the molecular dihedral angle from 37.33° to 0°, thereby optimizing molecular coplanarity and prolonging the photogenerated charge carrier lifetime by 820% compared to TAPT-TPD COFs devoid of Nc-TRs. Our findings further reveal that TAPT-DHBD COFs exhibit 5.0-fold and 3.6-fold enhancements in H 2 O 2 photocatalytic conversion kinetics and solar-to-chemical conversion (SCC) efficiency, respectively, relative to TAPT-TPD COFs. We further demonstrate that H 2 O 2 solutions generated in the flow-type photocatalytic system under solar irradiation exhibit a record-high antibacterial efficacy of 10 7 cfu s −1 , and achieve a 100% wound healing rate within 7 d, markedly outperforming commercial physiological saline.